Talent development practices and work engagement of in-service teachers at a private university in Western Uganda - Mugizi, Wilson; Ogaga Dafiewhare, Augustina; Manyange, Michael; Kiyundo Zikanga, Dinensio (Journal of Educational Research and Reviews, 2020)
Work engagement is the positive fulfilling work-related state of mind that is characterised by vigour, dedication and absorption. This study investigated factors that promote work engagement of teachers in schools looking at talent management practices. The talent management practices considered were performance appraisal, training and promotion. Specifically, the study examined the relationship between talent development practices and work engagement of in-service primary teachers at a private university in Western Uganda. In particular, the study sought to establish the relationship between performance appraisal, training, promotion and work engagement of in-service teachers. The study adopted a correlational research design to carry out the study. A self-administered questionnaire was used to collect data from 120 in-service teachers. The study findings revealed that for work engagement aspects, employee vigour and dedication of in-service teachers were high whereas absorption was moderate. With respect to talent management practices, performance appraisal and training were high but promotion was moderate. Regression analysis revealed that performance appraisal, training and promotion had positive and significant relationships with work engagement. It was concluded that performance appraisal, training and promotion are important for work engagement of teachers. Therefore, it was recommended that practitioners and head teachers ensure that the performance appraisal requirement is implemented effectively. Practitioners and head teachers should also ensure that teachers are offered regular training and are encouraged to go for further studies. Additionally, practitioners should implement a transparent promotion process that is regular.
Keywords: Work engagement; In-service teachers; Performance appraisal; Promotion; Training